2021
DOI: 10.1021/acs.jpcc.1c01657
|View full text |Cite
|
Sign up to set email alerts
|

UiO-66 Metal–Organic Framework as an Anode for a Potassium-Ion Battery: Quantum Mechanical Analysis

Abstract: The natural abundance of potassium in the earth's crust is 1000 times higher than that of lithium, so energy technologies built on potassium are more sustainable. Potassiumion batteries have attracted considerable attention because of their relatively low cost and high operating potential, but questions remain about the best anode material for such batteries. Here, we report first-principles computations based on density functional theory to investigate the performance of the UiO-66 metal− organic framework as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 64 publications
5
11
0
Order By: Relevance
“…The optimized structures of UiO-66-Ti, UiO-66-Hf, and UiO-66-L are shown in Figures S1, S2, and . In UiO-66-M, the optimized supercell volume of UiO-66-Hf is 4505.6 Å 3 , which is close to that of UiO-66 (4559.8 Å 3 ) reported by Tang et al, while the volume of UiO-66-Ti supercell is 4204.5 Å 3 , smaller than that of UiO-66-Hf. The bond lengths of M–O in the M 6 O 4 (OH) 4 node (M = Ti, Zr, or Hf) are shown in Table .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The optimized structures of UiO-66-Ti, UiO-66-Hf, and UiO-66-L are shown in Figures S1, S2, and . In UiO-66-M, the optimized supercell volume of UiO-66-Hf is 4505.6 Å 3 , which is close to that of UiO-66 (4559.8 Å 3 ) reported by Tang et al, while the volume of UiO-66-Ti supercell is 4204.5 Å 3 , smaller than that of UiO-66-Hf. The bond lengths of M–O in the M 6 O 4 (OH) 4 node (M = Ti, Zr, or Hf) are shown in Table .…”
Section: Resultssupporting
confidence: 80%
“…In a UiO-66-Hf supercell, when all sites are occupied by K (Figure ), the volume expansion rate is 14.6%, slightly smaller than that of UiO-66 (16.2%). The maximum capacity of UiO-66-Hf is 490.3 mAh/g, which is smaller than that of UiO-66 (644 mAh/g), because the atomic mass of Hf is much larger than that of Zr. For the UiO-66-Hf with the maximum capacity, the re-optimization shows that the structure can be fully recovered after removing all K, which verifies the stability of UiO-66-Hf during charging.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Among those materials, metal organic frameworks (MOFs) are promising anodes for potassium storage, thanks to their merits of low cost, low density, multiple redox sites, and abundant porosity. 12,[27][28][29][30] Taking advantage of the sufficient inner space of MOFs, Li et al demonstrated that a novel rectangular-shaped [C 7 H 3 KNO 4 ] n MOF can be used as the anode for efficient potassium storage, 26 which maintained a specic capacity of 123 mA h g À1 aer 150 cycles at a current density of 50 mA g À1 . The abundant N-K/O-K coordination bonds through the MOF pores are responsible for the excellent electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, MOFs are being received huge research interest due to their distinct physicochemical properties, tunable structures, and superior surface areas integrated with excellent application-oriented morphologies. [147][148][149][150][151][152] A wide variety of MOFs-derived composites with various structures and morphologies have already been used and proved as efficient electrode candidates for battery systems (ie, LIBs, SIBs, etc). At present, they possess greater potential for effective potassium storage, hence mitigating the bottlenecks encountered by the traditional KIBs electrode materials.…”
Section: Metal-organic Framework-derived Carbon Anodesmentioning
confidence: 99%